Reactions to social videos in long-tailed macaques - Elisabeth H. M. Sterck; Sophie M. Kamp; Ive Rouart; Lisette M. van den Berg; Dian G. M. Zijlmans; Tom S. Roth; Brad J. Bushman (Animal Cognition, 2025)
Abstract Animals can obtain important social information by observing social interactions among conspecifics. Depending on the social content, such as familiarity with the conspecifics and the type of interaction, the receiver’s attention, and possibly also movement and stress response, might differ. Moreover, these behavioural responses may vary depending on the individual’s own characteristics. By showing video fragments with different social content (i.e., run, conflict, sit, groom) of group members and strangers, we measured the reaction of captive long-tailed macaques living in multi-generational groups. In addition, we explored how an individual’s social and self-directed behaviour in its social group was related to reactions to these videos. Subjects paid more attention to videos of group members than strangers, especially more subordinate and less stress sensitive (i.e., low stress response when observing natural aggression) individuals. Self-directed behaviour was higher for younger individuals seeing strangers, but not group members, and for individuals with high levels of baseline self-directed behaviour and little grooming. Regarding context, the monkeys paid more attention to videos with active and aggressive content compared to sitting and grooming videos. Altogether, monkeys living in multi-generational groups show high interest in gathering social information on group members, and this is modulated by their social role and personal ability to handle social situations.